Designing Public Library of Binjai City by Metaphorical Architecture - Imam Faisal Pane; Febrina (International Journal of Architecture and Urbanism, 2019)
The lack of public reading interest makes people rarely come to visit the public library. The public library of The Binjai city as a media to increase people's knowledge, in fact, that still using traditional planning and structuring and has a less comfortable atmosphere. The Binjai city public library requires to improve its facilities and infrastructures related to the standards of a public library, so that possible to increase people's interest in visiting the library. The designer can make several alternative approaches to design an object, one of that is a metaphorical approach. Choosing of metaphor theme is a theme approachment by taking the book as a visual form that applicated to an element of the building. The strong Malay culture of Binjai city as a local heritage can be applicated in designing the public library of Binjai City. The concept design of the Binjai City Public Library is applied to accommodate library services and activities. By taking a representation physical form of the book as part of the building construction, giving all facilities and services can be functioned to attract more people's attention to visit the library.